2018
DOI: 10.1016/j.micpath.2018.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic potential of a recombinant polyvalent DNA vaccine against pathogenic leptospiral infection

Abstract: Leptospirosis is a serious epidemic disease caused by pathogenic Leptospira species. The disease is endemic in most tropical and sub-tropical regions of the world. Currently, there is no effective polyvalent vaccine for prevention against most of the circulating serovars. Moreover, development of an efficient leptospiral vaccine capable of stimulating cross-protective immune responses against a wide range of serovars remains a daunting challenge. This, in part, is associated with the extensive diversity and va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…This multi-epitope DNA vaccine, administered in hamsters as a plasmid DNA vaccine, showed partial protection against lethal leptospires, induced both agglutinating and neutralizing antibodies, as confirmed by MAT and in vitro growth inhibition assays, and was capable of reducing renal colonization. Renal histopathological lesions were further analyzed and mild to moderate pathologies were found, in contrast to severe lesions observed in the control group ( 77 ). The immunogenic multi-epitope DNA vaccines represent an interesting approach, as epitopes from several immunogenic leptospiral proteins could be tested to develop a novel vaccine against leptospirosis.…”
Section: Multi-epitope Vaccinesmentioning
confidence: 99%
“…This multi-epitope DNA vaccine, administered in hamsters as a plasmid DNA vaccine, showed partial protection against lethal leptospires, induced both agglutinating and neutralizing antibodies, as confirmed by MAT and in vitro growth inhibition assays, and was capable of reducing renal colonization. Renal histopathological lesions were further analyzed and mild to moderate pathologies were found, in contrast to severe lesions observed in the control group ( 77 ). The immunogenic multi-epitope DNA vaccines represent an interesting approach, as epitopes from several immunogenic leptospiral proteins could be tested to develop a novel vaccine against leptospirosis.…”
Section: Multi-epitope Vaccinesmentioning
confidence: 99%
“…When Leptospires invade the human body, the immune system comprising of an innate arm responds immediately while an adaptive component develops much later (Garba et al, 2018). Immunity against Leptospira infection is thought to be humoral based.…”
Section: Diagnosis Of Leptospirosismentioning
confidence: 99%
“…The first human case of severe leptospirosis in Malaysia was diagnosed in 1927 (El Jalii and Bahaman, 2004). In recent years, an increase in the incidence of human leptospirosis in Malaysia has been observed to coincide with severe flooding in some major states, including Kelantan and Selangor (Garba et al, 2018). Similarly, over 18 antigenically distinct serovars have been identified among humans and animals in Malaysia based on the gold standard microscopic agglutination tests (Daud et al, 2018;Rahman et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Currently available vaccines for both medical and veterinary applications, which are predominantly whole-cell killed bacterins, can not protect against serovars not included in the vaccine preparations (Bashiru and Bahaman, 2018). Also, experimental evaluations have shown that Leptospiral vaccines can effectively prevent disease and reduce shedding after challenges with the serovar included in the vaccine (Lin et al, 2016;Garba et al, 2018b). However, there is a lack of cross-reactivity among antigenically distinct serovars, which further limits the ability of available vaccines to provide heterologous protection (Branger et al, 2005;Garba et al, 2018b).…”
Section: Introductionmentioning
confidence: 99%